Factors associated with persistence of African animal trypanosomiasis in Lango subregion, northern Uganda - Wangoola, Robert Mandela; Bardosh, Kevin; Acup, Christine Among; Susan, Welburn; Waiswa, Charles; James, Bugeza (Tropical animal health and production, 2019)
African animal trypanosomiasis (AAT) continues to inflict heavy losses on livestock production especially cattle in terms of decreased production and productivity in Uganda. AAT is a disease complex caused by tsetse fly-transmitted Trypanosoma brucei brucei, Trypanosoma brucei rhodesiense, Trypanosoma congolense, and Trypanosoma vivax. The disease is most important in cattle but also known to cause serious losses in pigs, camels, goats, and sheep. Several control measures including live bait technology, mass treatment of cattle with trypanocidal drugs, and deployment of tsetse traps have been used in the past 10 years, but the problem still persists in some areas. This necessitated an exploration of the factors associated with continue trypanosome infections in cattle, which are also known reservoirs for the zoonotic trypanosomiasis. A structured questionnaire was administered to 286 animal owners from 20 villages purposively selected from Lira, Kole, and Alebtong districts of Lango subregion to obtain information on the factors associated with persistence of infection. Over 50% of the respondents reported trypanosomiasis as a major challenge to their livestock. Land ownership (P = 0.029), type of livestock kept (P = 0.000), disease control strategy employed (P = 0.000), source of drugs (P=0.046), and drug preparation (P=0.017) were associated with persistent AAT infection. We recommend continued farmer sensitization on the threat of AAT and the available prevention and control options. The use of isometamidium chloride for prophylaxis against trypanosomiasis is highly recommended. There is also a need to foster qualified private veterinary drug supply in the region.